Minha luta : por uma poética religiosa da leitura - Dall’agnol, Charles (2019)
This dissertation derives from reading theory and consists of an analysis of Karl Ove Knausgård's work My Struggle, a description of a religious poetics in reading, and a creative text on the same theme. The work of the Norwegian author is an abundant source of dialogue with the theme of secular spirituality, which this work seeks to investigate aiming at a poetics of reading. In addition to the aforementioned author, the dissertation has as a theoretical foundation works of Georges Bataille, Maurice Blanchot and Marcel Proust. In the analysis and in the creative writing, this work accomplishes a description of a religious poetics for reading literature.